OPTIMALISASI KEAMANAN WIRELESS MENGGUNAKAN FILTERING MAC ADDRESS: OPTIMALISASI KEAMANAN WIRELESS MENGGUNAKAN FILTERING MAC ADDRESS - Firmansyah Firmansyah; Rachmat Adi Purnama; Rachmawati Darma Astuti (Universitas Palangka Raya, 2021)
The use 802.11 wireless-based network services have become one of the most widely used network services, this will be directly proportional to the security holes that are in the wireless network. The rise of access rights theft in wireless networks is due to the large number of software and tools available on the internet to read encryption in wireless security. To minimize the occurrence of theft of access rights in wireless networks can use a layered security system by implementing security Hotspot login and MAC Address Filtering. This layered wireless network security is able to block users who try to access the network. This is because the wireless network security system has verified access rights 2 (two) times by matching the username and password in the hotspot login with the physical address or MAC address of the client. From the research results obtained by clients who use a username and password with different devices can not access the computer network. So every client who wants to connect to the internet network must use a device that has registered its MAC Address and in accordance with user access rights and passwords in the Hotspot login